'I love this, I wish I could make this': Talking digital adventure games with Mark Yohalem. (1st June 2021) - Klaehn, Jeffery
A conversation with attorney and game developer Mark Yohalem about his passion for point-and-click adventure games, and how his experiences as a player and fan inspired him to pursue game writing, to co-found Wormwood Studios (with artist Victor Pflug and programmer James Spanos) and, in 2010, to develop Primordia, a classical point-and-click adventure game that has sold roughly a quarter-million copies. Additional topics discussed include the potential of digital games to encourage empathy and connection; gaming fan communities; suitability of games for storytelling; gaming journalism, reviews and analysis; and games and creative work in relation to connection, participation and engagement.